Si Antong antukin at ang kalo Anton and the pulley - Malicdem, Cerilina T. (Science supplementary materials for the k to 12 curriculum, 2014)
"Today, we have machines that can do almost everything. Yet, the moving parts of these devices are combintions of simple machines like lever, pulley, wheel and axle, inclined plane, wegde and screw. The story is about one of the simple machines - the pulley. It focuses on when and how a pulley is being used. It also shows how a pulley can help people in their work. Also, the importance of being observant and listening attentively to the teacher is given emphasis in this story."--Preface.